Introduction to the special issue on English language teaching in public primary schools in Latin America - Ramírez-Romero, José Luis; Sayer, Peter (Education Policy Analysis Archives, 2016)
The guest editors introduce the Special Issue on English Language Teaching in Public Primary Schools in Latin America by summarizing articles about public primary English language programs in six countries in Latin America: Argentina, Brazil, Chile, Columbia, Mexico, and Puerto Rico. They synthesize the main issues related to English education programs in the region and discuss the common trends and challenges addressed by the authors in the special issue.